Peran Orang Tua Dalam Membentuk Etika Komunikasi Remaja Putus Sekolah Di Jorong Sungai Rotan Nagari Batu Taba Kabupaten Agam - Rafik Putra; Junaidi Junaidi (Universitas Pahlawan Tuanku Tambusai, 2023)
This study focuses on how the role of parents in shaping the communication ethics of dropout adolescents in Jorong Sungai Rotan Nagari Batu Taba. Agam Regency This research is based on the issue of communication ethics for dropout adolescents, where dropout adolescents speak poorly and impolitely. rude, talking while doing other activities, not focusing on the other person, interrupting the conversation and not managing the intonation of the speaking tone. This study uses a descriptive qualitative method that seeks to explain the role of parents in shaping the communication ethics of dropout youth conducting interviews and observing informants related to this phenomenon. This research resulted in a discussion of the role of parents where parents often ignore, allow, pay less attention and do not interfere in their children's lives and parents sometimes react to a child's problem with emotion. And the factors that become an obstacle in forming the communication ethics of dropout teenagers is the lack of communication between parents and teenagers because of the busyness of parents, the absence of regulations in the family that require good communication ethics, the lack of self-motivation of dropout teenagers to have good communication ethics, the lack of attention and direct supervision from parents and the community, there are still many etiquette (manners) that are not fulfilled or violated, there are environmental influences and adolescent associations that are not good and there is an attitude of belittling things. Keywords: The Role of Parents, Communication Ethics and Out-of-school Adolescents